Hubungan Koordinasi Mata Kaki, Kekuatan Otot Tungkai, dan Daya Ledak Otot Tungkai terhadap Kemampuan Shooting dalam Permaianan Sepak Bola Siswa MAN 2 Kota Makassar - Herman Herman; Ariana Asri; Tamajarra Tamajarra (Gerak: Journal of Physical Education, Sports, and Health, 2021)
The results showed that; (1) There is a significant relationship between eye-foot coordination and shooting ability in the soccer game of MAN 2 Makassar City Students, with a value of r= 0.751 (ρ < = 0.05); (2) There is a significant relationship between leg muscle strength and shooting ability in the soccer game of MAN 2 Makassar City Students, with a value of r = 0.657 (ρ < = 0.05); (3) There is a significant relationship between leg muscle explosive power and shooting ability in the soccer game of MAN 2 Makassar City Students, with a value of r= 0.620(ρ < = 0.05); (4) There is a jointly significant relationship between eye-foot coordination, leg muscle strength and leg muscle explosive power on the shooting ability of the soccer game of MAN 2 Makassar City Students, with the determinant coefficient (R2) = 0.679 or 67.9 %.